The within-day and between-day reliability of using sacral accelerations to quantify balance performance. (January 2016) - Williams, Jonathan M.; Dorey, Christopher; Clark, Suzannah; Clark, Carol
Abstract: Objectives: To investigate the between-day and within-day reliability of a sacral mounted accelerometer to quantify balance performance and different balance metrics. Design: Experimental, cross-sectional. Setting: Laboratorial experiment. Participants: Thirty healthy volunteers. Main outcome measures: Balance tasks were double leg stance, tandem stance and single leg stance with eyes open and closed. Performance was measured by converting accelerations into path length (PL, length of the sway trace), jerk (jerkiness of sway trace) and root mean square (RMS) of the accelerations. Results: Within-day ICC for PL were excellent (mean 0.78 95%CI 0.68–0.89), with Jerk and RMS demonstrating means of 0.60 and 0.47, respectively. The mean percentage minimal detectable change (MDC) within-day were small for PL (mean 6.7%, 95%CI 5.3–8.1). Between-day ICC were good for PL (mean 0.61, 95%CI 0.50–0.71), but more varied for Jerk and RMS. The mean percentage MDC was small for PL (mean 6.1%, 95%CI 5.0–7.2). No significant differences were determined for measurements between-days for any metric or task. PL had the highest discriminatory value between the 8 tasks. Conclusions: The sacral mounted accelerometer reliably measured balance performance within- and between-days. The PL is the recommended metric as it was the most reliable, most discriminatory and most sensitive to change. Highlights: Balance performance can be reliably measured using a sacral mounted balance sensor. This study recommends quantification of balance using path length (PL). Findings show changes in PL of more than 7–10% represents true change in performance.